PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. DELTA MULTI HADE SUKSES - Dahlan Ramdhani (JURNAL BISNIS dan TEKNOLOGI, 2023)
This research was conducted at PT Delta Multi Hade Sukses Cimareme West Bandung, a national private company which is a warehouse that stores several brands of drinks that will be distributed to every region in Indonesia, especially in the West Java Region,.The variables in this study are work discipline and work motivation as independent variables and performance as the dependent variable. The data in this study were obtained through the answers of 40 respondents to the questionnaire given. The research design uses descriptive and associative analysis. Associative analysis using multiple regression analysis. The author does not use statistical hypotheses because the population is the same as the sample. The research results obtained are as follows: 1) Work Discipline has a positive and significant influence on performance where the magnitude of the effect is 0.517, which means if Work Discipline is increased by 1 unit, then performance will increase by 0.517 units; 2) Work motivation has a positive and significant effect on performance. where the magnitude of the effect is 0.430, which means that if work motivation is increased by 1 unit, performance will increase by 0.430 units; 3) The effect of work discipline and work motivation on performance is 65.4%, while the remaining 34.6% is influenced by other variables.